Chromic textiles: Colour fastness properties and irreversible colour change behaviour of textiles screen printed with thermochromic, photochromic and hydrochromic colourants. (16th December 2022) - Cabral, Isabel; Santiago, Diana; Steffens, Fernanda
Abstract: The objective of this work was to study how ultraviolet (UV) light exposure, washing and rubbing can influence colour and dynamic qualities of chromic textiles, and to explore how the results attained can be applied by designers for the development of colour changing palettes. The experimental work was conducted with 74% polyamide and 26% elastane elastics screen printed with thermochromic, photochromic and hydrochromic pigments in diverse colours. Initially, colourfastness properties of each pigment type versus colour were assessed. Although washing and rubbing can interfere in samples' colours by becoming lighter at different degrees, the results attained highlight the poor stability to lighting of thermochromic and photochromic pigments, which also present changes between hues along exposure time. For conventional textile applications, poor colour fastness commonly represents a limitation. This work proposes that the way textile colours and behaviour are permanently affected by the studied conditions can be interpreted as a creative variable in the design process. Research samples with a combination of pigments were developed and tested with a combination of cycles of different fastness tests, namely one washing cycle for every 4 h of UV light exposure, totalling 48 h and 12 washing cycles. Results demonstrate the possibility of creating interactive surfaces capable of displaying a wide range of colours that evolve to static within different hues, over stimuli conditions.